Rethinking Tourism Public Policies to mitigate the effects of Covid-19 - Apaza-Panca, Cynthia Milagros; Santa-Cruz Arévalo, Johanna Elena; Maquera-Luque, Pedro Jesús; Ticona-Carrizales, Lucio (Cuestiones Políticas, 2020)
The objective of the research was to examine and analyze the articles that address public tourism policies in specialized magazines at a global level, with the aim of knowing through comparative public policies, alternative solutions in a post-pandemic scenario. Regarding the methodology, articles were selected whose titles presented one or more keywords that referred to the disease "Covid-19" and "public tourism policies" in Spanish and English. To process the information, the content analysis technique was used. The results showed that the place and space occupied by tourism public policies in the main tourism magazines is scarce and not seen as a management tool for the sector. The conclusion emphasized the lack of clarity regarding the methodology used in the articles and the scarce proposal of public policies that were implemented in situations of health crises, epidemics, wars, etc. For the rest, the following questions served as a guide for the analysis: 1) What is the role of governments in the tourism sector? and, 2) What public policies did governments implement in similar situations such as the current health crisis?